إتجاهات الطلبة الموهوبين في مدارس الملك عبدالله الثاتي للتميز نحو المباحث العلمية - أبو صالح، فاديا أحمد; الطراونة، ردينة خضر إبراهيم (جامعة محمد خيضر بسكرة - كلية العلوم الإنسانية والاجتماعية, 2020)
هدفت هذه الدراسة إلى التعرف على اتجاهات الطلبة الموهوبين في مدارس الملك عبد الله الثاني للتميز في الأردن نحو المباحث العلمية، كما هدفت الدراسة إلى معرفة الفروق في الاتجاهات وفقا لمتغيري الجنس والصف. ومن أجل تحقيق أهداف هذه الدراسة، تم اختيار عينة مكونة من (268) طالبا وطالبة من الصفين السابع والثامن الأساسي، وطبق عليهم مقياس الاتجاهات نحو المباحث العلمية. أشارت نتائج هذه الدراسة إلى أن الاتجاهات كانت إيجابية بشكل كبير جدا، وأنه لا توجد فروق في الاتجاهات تعزى لمتغيري الجنس والصف.
This study aimed to identify the attitudes of gifted students in King Abdullah II schools of excellence towards scientific courses also, identify the differences in the attitudes towards scientific courses according to the variables of (sex and grade). To achieve the study aims, a sample that consisted of (268) male and female students was chosen from the seventh and eighth grades in King Abdullah II schools of excellence. The questionnaire of attitudes towards scientific courses was electronically applied. The results revealed that the attitudes of the students of King Abdullah II schools of excellence towards the scientific courses were significantly positive and that there are no differences in these attitudes due to the variables of sex and grade.
Keywords: السياسة التعليمية -- المؤسسات التعليمية -- مدارس الملك عبدالله الثاني للتميز -- المباحث العلمية -- الأردن